A NARX Neural Network Model to Predict One-Day Ahead Movement of the Stock Market Index of Malaysia - Dhafer A.H.; Nor F.M.; Hashim W.; Shah N.R.; Bin Khairi K.F.; Alkawsi G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Commerce; Costs; Electronic trading; Financial markets; Investments; Commodity exchange; Commodity prices; Day-ahead; Exchange rates; Input variables; Model prediction; NARX; Neural-networks; Prediction performance; Stock market; Forecasting